Calculation method of dewatering settlement in saturated loess stratum - Guohua DENG; Huyan GAO; Jianguo ZHENG; Wenlong YU; Jiawei KANG (Shuiwen dizhi gongcheng dizhi)
In the construction of underground engineering with complex surrounding environment, reasonable prediction and evaluation of the influence of precipitation on the surrounding environment is a key problem to control the feasibility of the project. At present, the calculation of dewatering-induced settlement using the layered summation method heavily relies on empirical coefficients, leading to significant variability in predictions and deviations from actual observations. To predict the precipitation settlement of loess reasonably and accurately, based on the analysis of the physical properties of saturated loess, the void ratio and liquid index were introduced as key indicators to characterize both deformation potential and the deformation’s difficulty in the dewatering process. The practical calculation method of dewatering settlement of saturated loess stratum was established, and settlement verification was carried out at multiple sites. The results show that depending on the overlying pressure and groundwater action mode, saturated loess can form uncompacted saturated loess and compact saturated loess. The physical properties and dewatering settlement deformation of the two types of loess are different. The main physical property indexes affecting dewatering deposition deformation are the porosity ratio and liquid property index in the initial state, reflecting the deformation potential and the difficulty of deformation of saturated loess, respectively. The comparison between the calculation and measurement of six sites shows that the dewatering subsidence in the loess area mainly occurs in compact saturated loess where the macroporous structure still exists. The proposed e-IL method, incorporating void ratio and liquid index, effectively captures the settlement behavior of saturated loess. This study provides effective technical method for designing and constructing dewatering engineering in the loess area.